Covert Brain Infarction as a Risk Factor for Stroke Recurrence in Patients With Atrial Fibrillation. Issue 1 (21st October 2022) - Kim, Do Yeon; Han, Seok-Gil; Jeong, Han-Gil; Lee, Keon-Joo; Kim, Beom Joon; Han, Moon-Ku; Choi, Kang-Ho; Kim, Joon-Tae; Shin, Dong-Ick; Cha, Jae-Kwan; Kim, Dae-Hyun; Kim, Dong-Eog; et al.
Abstract : Background: We aimed to evaluate covert brain infarction (CBI), frequently encountered during the diagnostic work-up of acute ischemic stroke, as a risk factor for stroke recurrence in patients with atrial fibrillation (AF). Methods: For this prospective cohort study, from patients with acute ischemic stroke hospitalized at 14 centers between 2017 and 2019, we enrolled AF patients without history of stroke or transient ischemic attack and divided them into the CBI (+) and CBI (−) groups. The 2 groups were compared regarding the 1-year cumulative incidence of recurrent ischemic stroke and all-cause mortality using the Fine and Gray subdistribution hazard model with nonstroke death as a competing risk and the Cox frailty model, respectively. Each CBI lesion was also categorized into either embolic-appearing (EA) or non-EA pattern CBI. Adjusted hazard ratios and 95% CIs of any CBI, EA pattern CBI only, non-EA pattern CBI only, and both CBIs were estimated. Results: Among 1383 first-ever stroke patients with AF, 578 patients (41.8%) had CBI. Of these 578 with CBI, EA pattern CBI only, non-EA pattern CBI only, and both CBIs were 61.8% (n=357), 21.8% (n=126), and 16.4% (n=95), respectively. The estimated 1-year cumulative incidence of recurrent ischemic stroke was 5.2% and 1.9% in the CBI (+) and CBI (−) groups, respectively ( P =0.001 by Gray test). CBI increased the risk of recurrent ischemic stroke (adjusted hazard ratio [95% CI], 2.91 [1.44–5.88]) but did not the risk of all-cause mortality (1.32 [0.97–1.80]). The EA pattern CBI only and both CBIs elevated the risk of recurrent ischemic stroke (2.76 [1.32–5.77] and 5.39 [2.25–12.91], respectively), while the non-EA pattern only did not (1.44 [0.40–5.16]). Conclusions: Our study suggests that AF patients with CBI might have increased risk of recurrent stroke. CBI could be considered when estimating the stroke risk in patients with AF.